A clinical palpation test to check the activation of the deep stabilizing muscles of the lumbar spine - Hides, J. A.; Jull, G.; Richardson, C. (International SportMed Journal, 2000)
Segmental stabilization training (SST) is an exercise approach that has been developed to target muscles associated with the control of stability of the spinal segments. The basis of the concept is to teach patients to co-contract the transversus abdominis and multifidus muscles independently of the global muscles, with the aim of decreasing low back pain, disability, and recurrence. A clinical palpation test can be used to monitor co-contraction of the deep muscles during SST.